2010
DOI: 10.3329/bjp.v5i2.7592
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extracts of the leaves of Sesbania sesban reduces development of diabetic nephropathy in streptozotocin-induced diabetic rat

Abstract: The renal protective effect of the aqueous extract of Sesbania sesban leaves (250 and 500 ing/kg/day) in streptozotocin-induced diabetic rats were studied. Diabetic rats showed severe hyperglycemia with marked^ increase in proteinuria and albuminuria. Thye aqueous extract reduced proteinuria, albuminuria, lipid and glycated hemoglobin (HbAlc) deposition in diabetic rats. Histopathology studies on kidneys of diabetic rats " revealed severe increase in mesangial cells and matrix of glomeruli with hyaline thicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…According to the literature, this plant was used in ancient Indian medicine, where crushed seeds were used to treat boils and inflammations (Olajide et al, 2004). In general, the literature reports its empirical use for diabetes, lipid disorders, diarrhea, ulcers, stomach bleeding, hematuria, rheumatism, asthma, hypertension, pulmonary infections and chronic ophthalmia (Pandhare et al, 2012a;Zeid et al, 2012;Mujahid et al, 2013;Godoi et al, 2014;Moniruzzaman et al, 2015;Dissanayake et al, 2018) and cancer (Lindamulage and Soysa, 2016). Zeid et al (2012) reported its use as a tonic.…”
Section: Ethnomedicinal Usementioning
confidence: 99%
See 4 more Smart Citations
“…According to the literature, this plant was used in ancient Indian medicine, where crushed seeds were used to treat boils and inflammations (Olajide et al, 2004). In general, the literature reports its empirical use for diabetes, lipid disorders, diarrhea, ulcers, stomach bleeding, hematuria, rheumatism, asthma, hypertension, pulmonary infections and chronic ophthalmia (Pandhare et al, 2012a;Zeid et al, 2012;Mujahid et al, 2013;Godoi et al, 2014;Moniruzzaman et al, 2015;Dissanayake et al, 2018) and cancer (Lindamulage and Soysa, 2016). Zeid et al (2012) reported its use as a tonic.…”
Section: Ethnomedicinal Usementioning
confidence: 99%
“…The conclusions of the study exhibited that ethyl acetate fraction and n-butanol fraction of the ethanolic extract can adequately control the blood lipid levels in dyslipidemic situations by interfering with the biosynthesis of cholesterol and utilization of lipids. A study conducted by Pandhare et al (2012a) investigated the antihyperglycemic and antihyperlipidemic effects of A. pavonina seed aqueous extract in rats.…”
Section: Antihypertensive Activitymentioning
confidence: 99%
See 3 more Smart Citations